Eccentricity in Order to Re-centre: La Maison Rouge. (1st June 2015) - Bal, Mieke
In the ten years of its existence, La Maison Rouge has been an influential venue in the Paris art world. Besides monographic shows, it has organized innovative exhibitions through three different pathways: internationalization, the inclusion of 'art brut' and other materials made by or representing psychiatric patients, and the presentation of private collections. These exhibitions were all curated carefully on the basis of thoughtful principles. Paradoxically, the institution's anniversary exhibition Le mur seemed to undermine the very idea of curating by consigning the selection and arrangement of artworks to a computer. This article seeks to understand the paradox this curatorial methodology raises, and posits that eccentricity can be construed as a meaningful basis for constructing exhibitions.